Pengaruh Financial Distress Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Damayanti, Yulia; Atikah, Siti; Lenap, Indria Puspitasari (Universitas Dian Nuswantoro, 2023)
The goal of the research is to investigate the impact of financial hardship on company value and also to test profitability's potential to mitigate the impact of financial crisis on firm value. The present research employs a quantitative technique that makes use of secondary data from the yearly filings of property and real estate corporations. This study's population consists of 84 property and real estate corporations registered via the IDX from 2018 to 2021. The sample for this research was gathered by a purposive sampling strategy, yielding a sample of 41 firms and 164 observations. The classic assumption test, t test, coefficient of determination test, and employing moderated regression analysis with SPSS are all data analysis procedures. According to the studies, financial distress has a considerable negative effect on business value, and profitability amplifies the financial influence distress on company value.